Remote sensing and GIS applications in historical research. Case of The establishment of the Tiaret city (Algeria) during the colonial era - Asnoune, Salah (Technium Social Sciences Journal, 2023)
The present research paper is a descriptive study of the most essential natural geographic factors that distinguish the location of the city of Tiaret and the surrounding lands, shedding light on the extent of their importance and impact on the emergence of the colonial city, and the relationship of the physical characteristics of the location to the pattern and shape of the urban growth of the city during the colonial era and to the rest of human activities in it, especially agriculture. Moreover, the study also aims to highlight the effectiveness of employing remote sensing techniques and geographic information systems (GIS) as a support and investigation tool for this historical research, which was used as a geographical method through which the researcher is assisted in scrutinizing some of the data and information contained in some previous research related to the geography of the city of Tiaret from the topography, the surface, climate, and hydrography.